2023
DOI: 10.1093/ehjcr/ytad077
|View full text |Cite
|
Sign up to set email alerts
|

Hamartoma of mature cardiomyocytes presenting with atypical angina, 18F-fluorodeoxyglucose positron emission tomography uptake, and myocardial bridging: a case report

Abstract: Background Hamartoma of mature cardiomyocytes is a rare tumor and the present case shows a complex diagnostic pathway to understand its nature and treatment options in a young patient. The myocardial bridge was also part of the clinical evaluation discovered during the diagnostic workout. Case summary A 27-year-old woman with atypical chest pain and diffuse electrocardiographic changes received the diagnosis of neoformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…Globally, these findings imply that population diversity and inclusion in analyses always matter, as numbers keep varying both on autopsy [14][15][16][17] and angiogram. [18][19][20][21] MBs tend to be localized more in the left system, and Loukas et al 15 found it to be coronary artery dominance-dependent in their sample; however, MBs over the right coronary artery are also described, 22 while concomitant presence with a quadricuspid aortic valve, 23 transposition of great arteries, 24 hamartoma, 25 Takotsubo and spontaneous coronary artery dissection 26,27 have recently been reported.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Globally, these findings imply that population diversity and inclusion in analyses always matter, as numbers keep varying both on autopsy [14][15][16][17] and angiogram. [18][19][20][21] MBs tend to be localized more in the left system, and Loukas et al 15 found it to be coronary artery dominance-dependent in their sample; however, MBs over the right coronary artery are also described, 22 while concomitant presence with a quadricuspid aortic valve, 23 transposition of great arteries, 24 hamartoma, 25 Takotsubo and spontaneous coronary artery dissection 26,27 have recently been reported.…”
mentioning
confidence: 98%
“… 14 - 17 quanto na angiografia. 18 - 21 As PMs tendem a se localizar mais no sistema esquerdo, e Loukas et al, 15 descobriram que é dependente da dominância da artéria coronária em sua amostra; no entanto, PMs sobre a artéria coronária direita também são descritas, 22 enquanto presença concomitante com valva aórtica quadricúspide, 23 transposição de grandes artérias, 24 hamartoma, 25 Takotsubo e dissecção espontânea da artéria coronária 26 , 27 foram recentemente relatados.…”
unclassified